The Integration of Deep Learning in Thematic Learning at Elementary Schools: A Case Study at SD Negeri 03 Rawaheng Banyumas - Donny Khoirul Azis; Dwi Safitri Agustina; Irfan Musonif (IAIN Batusangkar, 2026)
This study aims to explore the process of integrating a pedagogical deep learning approach into integrated thematic learning design in elementary schools. This research employed a qualitative case study conducted at SD Negeri 03 Rawaheng Banyumas from January to February 2026. The participants included the principal, teachers, and students selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and documentation, including lesson plans and student work. The data were analyzed using thematic analysis through data reduction, data display, and conclusion drawing, supported by source and technique triangulation. The findings reveal that the integration of deep learning is implemented through structured stages of stimulus, exploration, discussion, and reflection. Contextual stimuli encouraged students to identify real-life problems, exploratory activities enabled direct interaction with the learning environment, collaborative discussions facilitated the exchange of ideas, and reflective sessions helped students connect concepts with personal experiences. These processes fostered contextual learning experiences and strengthened students’ cognitive, emotional, and social engagement, leading to deeper meaning-making. The findings support constructivist and meaningful learning theories by demonstrating that reflection plays a crucial role in helping students internalize and apply knowledge contextually. This study implies that deep learning-based thematic instruction can serve as an effective strategy for promoting meaningful and student-centered learning in elementary education. Keywords: pedagogical deep learning; thematic learning; meaningful learning; student engagement; elementary school